MITIGATION EDUCATION TO IMPROVE READINESS AMONG STUDENTS AT SDN NEGLASARI KERTASARI SUBDISTRICT BANDUNG REGENCY (GEOAREA | Jurnal Geografi, 2026)
This study aims to analyze the effect of earthquake disaster mitigation education programs in improving preparedness and reducing the level of psychological trauma among students after the earthquake that occurred in 2024 at SDN Neglasari, Kertasari District. The method used in this study was quantitative, with the population consisting of 140 students at SDN Neglasari. Data were obtained from a sample of 76 respondents selected using cluster sampling techniques, 3 homeroom teachers, and interviews with the principal. Data analysis techniques used simple linear regression using SPSS software to examine the relationship between the disaster mitigation education variable (X) and the psychological trauma variable (Y). The results showed that there was a significant effect of disaster mitigation education on increasing student preparedness and reducing psychological trauma levels. This was evidenced by a significance value of p-value (Sig.) = 0.000 < 0.05 and a coefficient of determination value of R = 0.722, which indicated the contribution of disaster mitigation education in explaining the dependent variable. The conclusion of this study is that disaster mitigation education is an effective strategic step to prepare students to be physically and psychologically ready and resilient in facing natural disasters.